A Novel Prognostic Signature for Survival Prediction and Immune Implication Based on SARS-CoV-2–Related Genes in Kidney Renal Clear Cell Carcinoma - Huang, Yongbiao; Chen, Sheng; Xiao, Lingyan; Qin, Wan; Li, Long; Wang, Yali; Ma, Li; Yuan, Xianglin (Frontiers in Bioengineering and Biotechnology, 2022)
Kidney renal clear cell carcinoma (KIRC) is a common aggressive malignancy of the urinary system. COVID-19, a highly infectious and severe disease caused by SARS-CoV-2, has become a significant challenge for global public health. Cancer patients have been reported to be more vulnerable to SARS-CoV-2 infection, and have a higher risk for serious complications than the general population. However, the correlation between KIRC and COVID-19 remains incompletely elucidated. In this study, we comprehensively investigated the expression and prognostic significance of 334 SARS-CoV-2 infection related genes in KIRC using the TCGA dataset, and identified 31 SARS-CoV-2 related differently expressed genes between KIRC and normal renal tissues. Based on these genes, we constructed and validated a 5-gene prognostic signature to distinguish low- and high- risk KIRC patients of poor survival in TCGA and E-MTAB-1980 cohorts. Gene set enrichment analysis (GSEA) showed that some inflammatory/immune-related pathways were significantly enriched in high-risk group. The ESITIMATE analysis indicated that patients in high-risk group had higher stromal and immune cell scores, therefore lower tumor purity. Moreover, they presented higher proportions of macrophages M0, T cells regulatory (Tregs) and T cells follicular helper and higher expression of CTLA-4, LAG-3, TIGIT and PDCD1 than low-risk patients. Besides, we also developed a nomogram to expand clinical applicability, which exhibits excellent predictive accuracy for survival. In conclusion, we identified a novel prognostic signature and nomogram based on SARS-CoV-2 related genes as reliable prognostic predictors for KIRC patients, and provided potential therapeutic targets for KIRC and COVID-19.